Diagnostik und Therapie von Tuberkulose unter Immuntherapien für Multiple Sklerose: aktueller Stand und Empfehlungen in Deutschland = Diagnostics and treatment of tuberculosis under immunotherapy for multiple sclerosis : current status and recommendations in Germany - Bittner, Stefan; Engel, Sinah; Lange, Christoph; Weber, Martin S.; Haghikia, Aiden; Luessi, Felix; Korn, Thomas; Klotz, Luisa; Bayas, Antonios; Paul, Friedemann; Heesen, Christoph; Stangel, Martin; et al. (Der Nervenarzt, 2019)
After years of low incidence, a large increase of new tuberculosis (TB) cases has been reported in Germany since 2015. New immunotherapies for the treatment of multiple sclerosis (MS) are associated with a reduced immune competence and a potential increased risk for infections. Most neurologists lack specific experiences with TB infections. This article summarizes specific recommendations for the diagnostics and treatment of TB under MS immunotherapies with a focus on the situation in Germany. Due to low case numbers and little experience with the risk of TB under the new immunotherapies, the clinical competence network for MS (KKNMS) consensus recommendations have a low grade of evidence.
Gesehen am 16.11.2020